Clinical significance of repeat blood cultures during febrile neutropenia in adult acute myeloid leukaemia patients undergoing intensive chemotherapy. Issue 10 (3rd October 2017) - Kimura, Shun-ichi; Gomyo, Ayumi; Hayakawa, Jin; Tamaki, Masaharu; Akahoshi, Yu; Harada, Naonori; Ugai, Tomotaka; Kusuda, Machiko; Kameda, Kazuaki; Wada, Hidenori; Ishihara, Yuko; Kawamura, Koji; et al.
Abstract: Background: We evaluated the clinical significance of repeat blood cultures in persistent and recurrent fever during neutropenia in adult acute myeloid leukaemia (AML) and myelodysplastic syndrome (MDS) patients undergoing intensive chemotherapy. Methods: We retrospectively reviewed the chemotherapy cycles at our centre between January 2007 and December 2015. Blood cultures obtained within three days after initial febrile neutropenia (FN) were defined as initial blood cultures and those obtained on or after day 4 were defined as repeat blood cultures. Results: Overall, 321 chemotherapy cycles in 89 patients were subjected to review. FN was identified in 276 (86.0%) chemotherapy cycles. In persistent FN (134 episodes), the causative pathogens were detected by repeat blood cultures in seven episodes (5.2%), including only three episodes (2.2%) of new infection. Shaking chills and high body temperature were identified as significant predictors for bloodstream infection (BSI). In recurrent FN (85 episodes), the causative pathogens were detected in seven episodes (8.2%), and all of these were new organisms. The frequency of detecting new pathogens by repeat blood cultures in recurrent FN (7/85) was higher than that in persistent FN (3/134) ( p  = .0491). A history of recent BSI was identified as a significant predictor for BSI in recurrent FN. Conclusions: The diagnostic yield of repeat blood cultures for persistent FN was low in intensive chemotherapy for AML and MDS. The frequency of repeat blood cultures for persistent FN could be reduced based on predictors. On the other hand, blood cultures were considered to be essential in cases with recurrent FN.